Comparison between deterministic and probabilistic approach in predicting the remaining strength of corroded pipelines - 484372 Nordin Yahaya; Norhazilan Md. Noor; World Engineering Congress (2nd : 2002 : Kuching, Sarawak) (Skudai : Universiti Teknologi Malaysia, 2002)
07